Is childhood immunisation associated with atopic disease from age 7 to 32 years? - Nakajima, Kazunori (BMJ Group, 2007)
BACKGROUND: There is ongoing conjecture over whether childhood immunisation leads to an increased risk of developing atopic diseases. OBJECTIVE: To examine associations between childhood immunisation and the risk of atopic disease. METHOD: Immunisation histories of 8443 Tasmanian children born in 1961 obtained from school medical records were linked to the Tasmanian Asthma Study. Associations between immunisation status and atopic diseases were examined while adjusting for possible confounders using multiple logistic regression. RESULTS: Diphtheria immunisation was weakly associated with an increased risk of asthma by age 7 years (odds ratio (OR) 1.3, 95% confidence interval (CI) 1.1 to 1.7), but there was no evidence of any association for four other vaccinations studied. An increased risk of eczema by age 7 years was associated with immunisation against diphtheria (OR 1.5, 95% CI 1.1 to 2.1), tetanus (OR 1.5, 95% CI, 1.1 to 2.0), pertussis (OR 1.5, 95% CI 1.1 to 1.9) and polio (OR 1.4, 95% CI 1.0 to 1.9) but not small pox. Similar but slightly weaker patterns of association were observed between the risk of food allergies and immunisation against diphtheria (OR 1.5, 95% CI 1.0 to 2.1), pertussis (OR 1.4, 95% CI 1.1 to 1.9), polio (OR 1.4, 95% CI 1.00 to 2.1) and tetanus (OR 1.30 95% CI 0.99 to 1.70), but not with small pox. There was no evidence of associations between immunisation history and hay fever, or incidence of later‐onset atopic outcomes. CONCLUSIONS: The few effects seen in this study are small and age‐dependent, and nearly all our findings support numerous previous studies of no effect of vaccines on asthma. Based on these findings, the fear of their child developing atopic disease should not deter parents from immunising their children, especially when weighed against the benefits.